Association of IL6 gene methylation in peripheral blood cells with the development and prognosis of autoimmune thyroid diseases - Nachi Hirai; Mikio Watanabe; Naoya Inoue; Riku Kinoshita; Hiroki Ohtani; Yoh Hidaka; Yoshinori Iwatani (Taylor & Francis Group, 2019)
Autoimmune thyroid diseases (AITDs), including Hashimoto's disease (HD) and Graves' disease (GD), are archetypes of organ-specific autoimmune diseases, but the prognosis of patients with AITD varies. Autoimmune diseases, including AITDs, are believed to develop in response to both genetic and environmental factors. Interleukin (IL)-6 plays a major role in B cell differentiation and T cell proliferation, and methylation of the IL6 gene is associated with IL-6 production. To clarify the role of IL6 gene methylation in the pathogenesis and prognosis of AITDs, we measured the methylation levels of −666, −664, −610, −491 and −426 CpG sites in the IL6 gene. We measured the methylation levels of 5 CpG sites in 29 patients with HD, 31 patients with GD and 16 healthy volunteers using pyrosequencing. The methylation level at each of the −664, −491 and −426 CpG sites was negatively correlated with the age at the time of sampling. Multiple regression analysis indicated that patients with HD, including severe or mild HD, showed higher methylation levels at the −426 CpG site than control subjects. Patients with intractable GD showed lower methylation levels at the −664 and −666 CpG sites than patients with GD in remission. In conclusion, IL6 gene methylation levels were related to the susceptibility to HD and the intractability of GD.